2020
DOI: 10.1002/pchj.352
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between social comparison and submissive behaviors in people with social anxiety: Paranoid social cognition as the mediator

Abstract: Biased evaluation fears and paranoid thoughts lead to various safety behaviors that are the cardinal features and perpetuating factors of social anxiety. The present study aimed to emphasize evaluative and paranoid thoughts that predispose and maintain this growing psychological condition. A cross-sectional research design was employed to explore the relationship between social comparison, paranoid social cognitions, and submissive behaviors in patients with social anxiety. Furthermore, predictive effects of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Research has shown that social hierarchy is linked to personality traits in both animals and humans ( Colléter and Brown, 2011 ; David et al, 2011 ; Dasgupta et al, 2022 ; Vékony et al, 2022 ). For example, dominant individuals tend to be more assertive, confident, and proactive ( Blanchard et al, 1988 ; Salonen et al, 2022 ), while submissive individuals are often more anxious, passive, and reactive ( Catarino et al, 2014 ; Zaffar and Arshad, 2020 ). In addition, social hierarchy can shape individual behavior and physiology ( Schmid Mast, 2010 ; Flota-Bañuelos et al, 2019 ) including stress responses ( Knight and Mehta, 2017 ; Karamihalev et al, 2020 ), brain activity ( Breton et al, 2014 ; Williamson et al, 2019a ), and gene expression ( Pohorecky et al, 2004 ; Horii et al, 2017 ; Lea et al, 2018 ; Williamson et al, 2019b ).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that social hierarchy is linked to personality traits in both animals and humans ( Colléter and Brown, 2011 ; David et al, 2011 ; Dasgupta et al, 2022 ; Vékony et al, 2022 ). For example, dominant individuals tend to be more assertive, confident, and proactive ( Blanchard et al, 1988 ; Salonen et al, 2022 ), while submissive individuals are often more anxious, passive, and reactive ( Catarino et al, 2014 ; Zaffar and Arshad, 2020 ). In addition, social hierarchy can shape individual behavior and physiology ( Schmid Mast, 2010 ; Flota-Bañuelos et al, 2019 ) including stress responses ( Knight and Mehta, 2017 ; Karamihalev et al, 2020 ), brain activity ( Breton et al, 2014 ; Williamson et al, 2019a ), and gene expression ( Pohorecky et al, 2004 ; Horii et al, 2017 ; Lea et al, 2018 ; Williamson et al, 2019b ).…”
Section: Discussionmentioning
confidence: 99%
“…As a special group, individuals with social anxiety disorder tend to have less positive bias than those without SAD. Although people often attribute positive events to internal and stable factors, this attribution tendency is difficult to be found in individuals with social anxiety disorder ( 21 , 22 ). They make internal attributions to negative events, believing that failure is their lack of ability but success has nothing to do with them ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…A similar report suggested that the character attributes assumed a part in figuring out who will be engaged with unfriendly practices and who keep away from such demonstrations. Exploration is expected to discover the variables and other individual contrasts that clarify why and how individuals act distinctively to saw antagonistic environments (Thoroughgood et al, 2019;Zaffar et al, 2020;McTiernan et al, 2020) This examination endeavors to investigate the distal impacts of antagonistic HOC that are sent to workers, to some degree, through PC and low sleep quality. Since, the unfriendly environment is a stressor to which workers may react by over reasoning and initiating distrustful discernment, which will additionally prompt low rest quality.…”
Section: Introductionmentioning
confidence: 99%